Epistolae mixtae: ex variis Europae locis ab anno 1537 ad 1556 scriptae (Monumenta Historica Societatis Jesu, 1898)
t. 1. 1537-1548 -- t. 2. 1549-1552 -- t. 3. 1553 -- t. 4. 1554-1555-- t. 5. 1555-1556 [1611].